Climatology and inter-annual variability of the polar mesospheric winds inferred from meteor radar observations over Sodankylä (67N, 26E) during solar cycle 24. (June 2018) - Lukianova, Renata; Kozlovsky, Alexander; Lester, Mark
Abstract: The inter-annual variability, climatological mean wind and tide fields in the northern polar mesosphere/lower thermosphere region of 82–98 km height are studied using observations by the meteor radar which has operated continuously during solar cycle 24 ( from December 2008 onward) at the Sodankylä Geophysical Observatory (67N, 26E). Summer mean zonal winds are characterized by westward flow, up to 25 m/s, at lower heights and eastward flow, up to 30 m/s, at upper heights. In the winter an eastward flow, up to 10 m/s, dominates at all heights. The meridional winds are characterized by a relatively weak poleward flow (few m/s) in the winter and equatorward flow in the summer, with a jet core (∼15 m/s) located slightly below 90 km. These systematically varying winds are dominated by the semidiurnal tides. The largest amplitudes, up to 30 m/s, are observed at higher altitudes in winter and a secondary maximum is seen in August–September. The diurnal tides are almost a factor of two weaker and peak in summer. The variability of individual years is dominated by the winter perturbations. During the period of observations major sudden stratospheric warmings (SSW) occurred in January 2009 and 2013. During these events the wind fields were strongly modified. The lowest altitude eastward winds maximized up to 25 m/s, that is by more twice that of the non-SSW years. The poleward flow considerably increases (up 10 m/s) and extends from the lower heights throughout the whole altitude range. The annual pattern in temperature at ∼90 km height over Sodankyla consists of warm winters (up to 200 K) and cold summers (∼120 K). Highlights: 8-yr of the meteor radar observations over Sodankyla are presented. Climatology and year-to-year characteristics of the mean zonal and meridional winds at 82–98 km height. Characteristics of the semidiurnal and diurnal tides.